Outcomes after Rehospitalization at the Same Hospital or a Different Hospital Following Critical Illness - Hua, May (Am J Respir Crit Care Med, 2017)
Rationale: Intensive care unit (ICU) patients who receive mechanical ventilation are at high risk for early rehospitalization. Given the medical complexity of these patients, a lack of continuity of care may adversely affect their outcomes during rehospitalization. Objectives: To determine whether outcomes differ for patients who are rehospitalized at a different hospital versus the hospital of their index ICU stay. Methods: We conducted a retrospective cohort study of mechanically ventilated ICU patients rehospitalized within 30 days in New York State hospitals between 2008 and 2013. Measurements and Main Results: We measured frequency of rehospitalization at a different hospital, mortality, length of stay, and costs during rehospitalization. Of 26,947 mechanically ventilated ICU patients rehospitalized within 30 days of discharge, 8,443 (31.3%) were rehospitalized at a different hospital than that of the index ICU stay. For patients at a different hospital, 13.7% died during rehospitalization versus 11.1% who died at the index hospital (adjusted rate ratio [aRR], 1.11; 95% confidence interval [CI], 1.03–1.20; P = 0.009). Patients who died at a different hospital had shorter length of stay (aRR, 0.80; 95% CI, 0.70–0.92; P = 0.001) and decreased costs (adjusted mean difference, −$9,632.73; 95% CI, −$16,387.60 to −$2,877.88; P = 0.005), whereas survivors of rehospitalization at a different hospital had a modest increase in length of stay (aRR, 1.06; 95% CI, 1.01–1.11; P = 0.009) and increased costs of care (adjusted mean difference, $1,665.34; 95% CI, $602.12–$2,728.56; P = 0.002). Conclusions: Almost one-third of mechanically ventilated critically ill patients were rehospitalized at a different hospital than that of the index ICU stay. This care discontinuity was associated with increased mortality.